Evaluation of Glutathione S Transferase ancl Glutathione Levels inSerum of Normal Individuals and Patients lvith Diabetes Mellitus - Riffat Sarhat, Entedhar (Tikrit Journal of Pharmaceutical Sciences, 2023)
Diabetes Mellitus (DM) is considered as a member of oxidative stress syndrome. It is associated with an imbalance between types of free radicals and scavenging system. Sixty patients with DM were studied for the changes in their Glutathione s- Transferase (GSTs) and Glutathjone (GSH) in the blood. Who attended out patient, and Primary health care In Tikrit Teaching Hospital in Tikrit City. This Study concluded that GST activities are significantly higher in serum of patients with type I and II diabetes mellitus disease than that of controls, P<0.05. But there rvas a significant decrease in levels of GSH activity in both types of diabetic patients. Key rvords: Glutathione s- Transferase (GSTs), Glutathione (GSH), & Diabetes Mellitus (DM).